INFLUENCE OF MAIZE HYBRIDS AND SEED SIZE AFTER PROCESSING ON THE PHYSICAL CHARACTERISTICS OF THE SEEDS, GERMINATION AND RACES GROWTH - Đokić, Dragoslav; Tabakovic, Marijenka; Perić, Vesna; Poštić, Dobrivoj; Štrbanović, Ratibor; Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2023)
In these studies, the physical, and qualitative characteristics of seeds of small (SF) and large fractions (KF) and seedlings’ vigour of five maize hybrids were presented; FAO 300 to FAO 600. The choice of hybrids and the fractions could not significantly (p ≥ 0.05) affect seed germination. Width, thickness, length, seed weight, dead seeds, abnormal seedling and growth and seedling mass of hybrids and fractions had a significant (p ≤ 0.05 to p ≤ 0.001) effect. Significant and positive dependence (p ≥ 0.001) between seed germination was achieved with the growth of stem, root and seedling weight, as well as with the weight of 1000 grains (p ≥ 0.01) and with the thickness (TS) (p ≥ 0.05). Seed germination with abnormal seedlings achieved a negatively (p ≥ 0.01) significant dependence. The effect of hybrids varied according to seed size on stem growth by 0.9 cm for SF and 1.7 cm for large fraction KF, on root growth by 3.4 cm for SF and 4.2 cm for KF, on seedling mass by 0.08 g for SF and 0.06 g for KF. Seed fraction KF, on average, for the tested maize hybrids, had 1.18 cm more stems, 2.94 cm longer roots and 0.032 g more seedling weight.